What to do... With Development? Neodevelopmentalisms, Goodliving and Popular Alternative - Féliz, Mariano (Sociedad y Economía, 2015)
Since Second World War, the history of capitalist development in the periphery has been marked by the developmentalist Project. With its crisis in the 1970s until the late 1990's, the hegemonic project went from substitutive industrialization to regressive neoliberal restructuring. The neoliberalism crisis in South America originated a new project marked by the dispute between new developmentalism of neo-structuralist matrix and the societal project of Buenvivir (Good living). This article analyzes the transformations of such projects in South America, focusing on the current debate (and social struggle) between Buenvivir and neodevelopmentalist projects.